Inovasi Pengembangan Kulit Macaron Menggunakan Tepung Kacang Hijau (Vigna radiata L.) Dengan Tepung Almond dan Penambahan Serbuk Black Mulberry (Morus nigra Sp.) - Taufik, Yusman; Gozali, Thomas; Nurminabari, Ina Siti; S, Ashifa Zahra (Jurnal Penelitian Pertanian Terapan, 2024)
The aim of this study was to obtain the results of the ratio of mung bean flour with almond flour and the addition of black mulberry powder on the characteristics of macaron shell.This research consists of two stages, namely preliminary research and main research. Preliminary research was conducted to make mung bean flour and black mulberry powder and then analyzed. The main research used a 3x3 factorial Randomized Block Design (RAK) with 3 replications. The treatment design consisted of two factors, namely the factor of the ratio of mung bean flour to almond flour (T) consisting of 3 levels (70:30), (60:40) and (50:50) and the factor of adding black mulberry powder (B) consisting of 3 levels 0%, 1% and 2%. The responses in this study consisted of chemical responses namely moisture content, ash content, fat content and protein content, physical responses of swelling power and color intensity, and organoleptic responses namely color, aroma, taste and texture attributes The results showed that the ratio of mung bean flour to almond flour had an effect on moisture content, ash, fat, protein, swelling power, color intensity (L* a* b* value), hedonic attributes of color, aroma, taste and texture. The addition of black mulberry powder had a significant effect of swelling power, color intensity (L* a* b* value), hedonic attributes of color, aroma, taste and texture. The interaction between the ratio of mung bean flour with almond flour and the addition of black mulberry powder had an effect of swelling power, color intensity (L* a* b* value), hedonic attributes of color, aroma, taste and texture.